2010
DOI: 10.1074/jbc.m109.074435
|View full text |Cite
|
Sign up to set email alerts
|

A CD36-related Transmembrane Protein Is Coordinated with an Intracellular Lipid-binding Protein in Selective Carotenoid Transport for Cocoon Coloration

Abstract: The transport pathway of specific dietary carotenoids from the midgut lumen to the silk gland in the silkworm, Bombyx mori, is a model system for selective carotenoid transport because several genetic mutants with defects in parts of this pathway have been identified that manifest altered cocoon pigmentation. In the wild-type silkworm, which has both genes, Yellow blood (Y) and Yellow cocoon (C), lutein is transferred selectively from the hemolymph lipoprotein to the silk gland cells where it is accumulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 52 publications
3
87
0
Order By: Relevance
“…Tissue distribution pattern of CR31 mRNA products were similar to that of CBP, while CR42 mRNA was expressed mainly in the gonad (see Figure 3). Similar to CBP expression patterns [10,13], expression of these transcripts was repressed in silk gland during the fourth instar (data not shown), suggesting a common mechanism of expression regulation on these genes and thus giving this special spatial-temporal expression pattern.…”
Section: Novel Cbp Transcripts Identified By 5' Race Analysismentioning
confidence: 50%
“…Tissue distribution pattern of CR31 mRNA products were similar to that of CBP, while CR42 mRNA was expressed mainly in the gonad (see Figure 3). Similar to CBP expression patterns [10,13], expression of these transcripts was repressed in silk gland during the fourth instar (data not shown), suggesting a common mechanism of expression regulation on these genes and thus giving this special spatial-temporal expression pattern.…”
Section: Novel Cbp Transcripts Identified By 5' Race Analysismentioning
confidence: 50%
“…For the B. mandarina individuals, the CBP copy number was found to be $1, with the exception of two Taiwanese individuals that were calculated to have copy numbers of $2. Our calculation also showed that the two Taiwanese individuals had approximately two copies of dib (Niwa et al 2005) and Cameo2 (Sakudoh et al 2010) (Figure 2, C and E), the control nuclear genes used for copy number quantification. Therefore, we concluded that B. mandarina most likely had only one copy of CBP, and the apparent duplication in the Taiwanese individuals may be due to an unexplained 50% decrease in the copy number of OR2 (Krieger et al 2003;Sakurai et al 2004), which was used for the normalization of all copy numbers in this study (for details of the normalization process, see materials and methods).…”
Section: Resultsmentioning
confidence: 86%
“…We speculate that a tendency of human nature to prefer unambiguous or pure colors may have caused the diversification of CBP structure from a duplicated allele to a null allele, resulting in the production of both deep yellow and clear white B. mori cocoons. On the other hand, it is noteworthy that cocoon color is also affected by genes other than CBP, such as Cameo2 (Sakudoh et al 2010) or UGT10286 (Daimon et al 2010). To properly evaluate the contribution of the changes of CBP structure to cocoon color, elucidation of the genetic diversity and domestication history of other cocoon color genes would be useful.…”
Section: Resultsmentioning
confidence: 99%
“…In the candidate region, C12, another NAT gene, is located adjacent to the candidate in mln, which raises the question of whether a defect of C12 might be responsible for the observed mln phenotype. We initially excluded C12 because of the lack of a coding mutation, but recent published work has shown evidence for regulatory mutation in the silkworm trait (Sakudoh et al, 2010). Comparative analysis indicated that the expression levels of C12 at the sites where melanism was seen (such as the larval head, the larval tail spot and the whole body of the adult) were essentially the same in the wild type and mln mutant (see Fig.…”
Section: Research Articlementioning
confidence: 99%